The use of chia seeds in the production of muffins made from sponge-fat dough - Adamczyk, Greta; Bobel (Zinchenko), Inna (My University, 2022)
Fat-sponge cakes are appreciated all over the world due to their simplicity, taste and wide range of products. The developed sponge-fat products contain chia seeds in their compositions were characterized by higher moisture than the control sample, which may indicate their water retention capacity during the baking process. Part of the vegetable oil (10-20%) in muffins can be successfully replaced by the addition of oilseeds, reducing the fat content and not deteriorating their texture.

Бісквітні вироби цінують у всьому світі завдяки їх простоті, смаку та широкому асортименту. Розроблені бісквітні вироби, що містять у своєму складі насіння чіа, характеризувалися вищою вологістю, ніж контрольний зразок, що може свідчити про їхню вологоутримуючу здатність під час процесу випікання. Частину рослинної олії (10-20%) у маффінах можна успішно замінити додаванням насіння олійних культур, зменшивши при цьому вміст жиру і не погіршивши їх текстуру.
Keywords: muffin; chia seeds; мафін; насіння чіа; кафедра технології хлібопекарських і кондитерських виробів